Enforcement of Criminal Elements in Administrative Actions: Implementasi Unsur Pidana dalam Tindakan Administratif - Junaidi, Muhammad (Indonesian Journal of Law and Economics Review, 2024)
This study employs a normative juridical approach to explore the intertwining of administrative actions and criminal accountability within the governance framework. By scrutinizing legal norms, the research assesses the objective position of criminal elements in administrative actions, revealing a tendency to prioritize formal aspects over legal validity. The findings highlight the conflation of criminal law with administrative proceedings, resulting in disparate consequences. Consequently, policymakers may shy away from necessary actions or seek alternative routes to avoid potential risks. This study underscores the imperative to delineate clear boundaries between administrative duties and criminal liabilities to foster more effective governance practices and mitigate unwarranted legal risks. Highlights : The study emphasizes the necessity of delineating clear boundaries between administrative actions and criminal liabilities. Prioritizing formal aspects over legal validity in administrative actions can lead to disparate consequences within governance frameworks. Policymakers may resort to alternative routes or hesitate to take necessary actions due to the conflation of criminal law with administrative proceedings. Keywords: Normative Juridical Approach, Administrative Actions, Criminal Accountability, Governance Framework, Legal Validity